2021
DOI: 10.1002/aoc.6327
|View full text |Cite
|
Sign up to set email alerts
|

Carbon–nitrogen bond formation using modified graphene oxide derivatives decorated with copper complexes and nanoparticles

Abstract: Several catalytic reactions such as Ullmann, Chan–Lam, Huisgen 1,3‐dipolar cycloaddition, [2 + 3] cycloaddition, condensation, and coupling reactions under suitable conditions have been used for the synthesis of fundamental structures containing a carbon–nitrogen (C–N) bond. Graphene oxide (GO) and its derivatives as heterogeneous catalysts have attracted considerable attention for the synthesis of organic building blocks. Loading of GO derivatives with copper complexes or nanoparticles, as one of the most abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 167 publications
(100 reference statements)
0
8
0
Order By: Relevance
“…103 Another strategy has also been developed for the cycloaddition of azide-alkyne systems with benzyl halides or epoxide analogues using the Cu 2 O/ rGO/TiO 2 nanomaterial to generate triazoles (Scheme 9). 104 TiO 2 based nanomaterials have also been used in asymmetric photocatalysis 105 for a variety of transformations such as hydrogenation of aromatic ketones 106 and alkylation. 46 The a-oxyamination of aldehydes was done with TiO 2 -P25 and chiral secondary amine catalysts in the presence of UV light (Scheme 10).…”
Section: Transition Metal Chalcogenides (Tmcs)mentioning
confidence: 99%
See 1 more Smart Citation
“…103 Another strategy has also been developed for the cycloaddition of azide-alkyne systems with benzyl halides or epoxide analogues using the Cu 2 O/ rGO/TiO 2 nanomaterial to generate triazoles (Scheme 9). 104 TiO 2 based nanomaterials have also been used in asymmetric photocatalysis 105 for a variety of transformations such as hydrogenation of aromatic ketones 106 and alkylation. 46 The a-oxyamination of aldehydes was done with TiO 2 -P25 and chiral secondary amine catalysts in the presence of UV light (Scheme 10).…”
Section: Transition Metal Chalcogenides (Tmcs)mentioning
confidence: 99%
“…103 Another strategy has also been developed for the cycloaddition of azide-alkyne systems with benzyl halides or epoxide analogues using the Cu 2 O/rGO/TiO 2 nanomaterial to generate triazoles (Scheme 9). 104…”
Section: Nanomaterials In Photo-mediated Organic Transformationsmentioning
confidence: 99%
“…It was found that very high yields are generally obtained for most of the heterogeneous catalysts reported, regardless of whether copper is already present in the catalyst 27,[53][54][55][56][57] in the required +1 oxidation state or is generated during catalysis. 14,24,51,52 In the latter case, either reducing agents 14,52 or photocatalytic reduction 24,51 were employed.…”
Section: Paper Dalton Transactionsmentioning
confidence: 99%
“…[17] It is an ideal S C H E M E 1 Synthetic schematic outline of CTD-GO support for the immobilization of metals, metal oxides, organic compounds, and inorganic complexes. [17][18][19] GO has a unique structure, good chemical and thermal stability, high surface area, good accessibility, and availability of various oxygenated functional groups on its surface that makes it amenable towards surface engineering. [17] Due to the ease of versatility of surface chemical modifications, GO has been employed with spectacular success in catalysis, drug delivery, environmental remediation, biomedical domain, and material science.…”
Section: Introductionmentioning
confidence: 99%